E-Learning Readiness and Attitudes Among Medical Students After Emergency Remote Education: A Cross-Sectional Study - Burcu Küçük Biçer; Özlem Coşkun (Academic Journal of Health, 2026)
Background and Aims: Emergency remote education during the COVID-19 pandemic transformed medical education and exposed differences in students' capacity to learn online. This study assessed medical students' attitudes toward e-learning and e-learning readiness after this compulsory experience and examined whether readiness was associated with attitude independently of demographic characteristics and digital access. Methods: This cross-sectional study included 656 students enrolled in years 1-5 at a medical school in Ankara, Türkiye. Attitudes were assessed with the 23 item Turkish Test of e-Learning Related Attitudes, and readiness with the 25 item Self-Assessment of Readiness for e-Learning scale. Associations were examined using Spearman correlation and multivariable linear regression. Results: The participation rate was 26.2%. The mean item scores were 2.86 ± 0.53 for attitude and 3.98 ± 0.55 for readiness. Readiness was strongly and positively correlated with e-learning attitude (Spearman rho=0.607, 95% CI 0.432-0.749, p